2018
DOI: 10.1016/j.chiabu.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Mediators between adverse childhood experiences and suicidality

Abstract: We investigated whether psychiatric symptomatology, impulsivity, family and social dysfunction, and alcohol use mediate the relationship between adverse childhood experiences (ACEs) and suicidality. The study population comprised 206 adolescent psychiatric inpatients and 203 age- and gender-matched adolescents from the community. ACEs and suicidality were assessed using the Schedule for Affective Disorders and Schizophrenia for School-Age Children - Present and Lifetime version, the Life Events Checklist, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
2
15
1
1
Order By: Relevance
“…Internalizing and externalizing behavior problems are two major developmental pathways that underlie the link between child maltreatment and suicidal ideation and behaviors in adolescence (Rytilä-Manninen et al, 2018; Wanner et al, 2012). However, to date, these two mechanisms have largely been modeled as independent processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internalizing and externalizing behavior problems are two major developmental pathways that underlie the link between child maltreatment and suicidal ideation and behaviors in adolescence (Rytilä-Manninen et al, 2018; Wanner et al, 2012). However, to date, these two mechanisms have largely been modeled as independent processes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the robust documentation on the link between child maltreatment and suicidal ideation and behaviors, there is relatively scant knowledge on the developmental mechanisms underlying this association. Several studies have identified internalizing and externalizing psychopathology as two separate mechanisms in the association between child maltreatment and suicidal ideation and behaviors in adolescence (e.g., Miller, Adams, Esposito-Smythers, Thompson, & Proctor, 2014; Rytilä-Manninen, Haravuori, Fröjd, Marttunen, & Lindberg, 2018; Wanner, Vitaro, Tremblay, & Turecki, 2012). However, emerging research suggests that some youth exhibit both internalizing and externalizing symptoms and that these concurrent symptom elevations are stable over time (Willner, Gatzke-Kopp, & Bray, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic experiences before age 18 have been demonstrated to have significant and profound effects on a wide range of mental health measures ( Kim et al, 2019 , Racine et al, 2018 ). For example, most previous studies have shown that early traumatic or adverse experience is strongly related to depression or psychiatric problems (e.g., suicidality) ( Merrick et al, 2017 , Rytila-Manninen et al, 2018 ). Belsky’s developmental hypothesis ( Belsky, 1993 ) provided a theoretical background for this relation and argued that the accumulation of various personal adversities throughout an individual’s life will synergistically create poor health consequences in later years.…”
mentioning
confidence: 99%
“…In fact, whether externalizing symptoms directly affect suicidality in adolescents has been a controversial issue. Some studies have reported that externalizing behaviors such as aggressive behavior and impulsivity could be a link between childhood trauma and suicidality in adolescents [ 64 66 ]. A previous study investigating the trajectory of high anxiety and high disruptiveness has reported that both trajectories independently affect the association between childhood trauma and suicide attempts [ 19 ].…”
Section: Discussionmentioning
confidence: 99%